SISTEM INFORMASI PADA PONDOK PESANTREN AL-QOSIM MUARO JAMBI: web-based, al-qosim boarding school, information system. - Suana, Irma (LP2M Universitas Nurdin Hamzah, 2018)
During this time the data processing system in the Al-Qosim Islamic Boarding School information system is still done manually. Where in the data processing system previously experienced many obstacles in the delivered of reports to the leadership, and felt inaccurate and efficient in the processing of data processing at the Muaro Jambi Al-Qosim Islamic Boarding School. Therefore, the authors identified, evaluated the problems and obstacles that occur so that can be proposed to improve it by developing it in the form of research with the title